High Altitude: Human Adaptation to Hypoxia - Swenson, Erik R.; Bärtsch, Peter (SpringerLink Bücher, 2014)
Over the last decade the science and medicine of high altitude and hypoxia adaptation has seen great advances. High Altitude: Human Adaptation to Hypoxia addresses the challenges in dealing with the changes in human physiology and the particular medical conditions that arise from exposure to high altitude. In-depth and comprehensive chapters cover both the basic science and the clinical consequences of exposure to high altitude. Genetic, cellular, organ and whole body system responses to high altitudes are covered and chapters discuss these effects on a wide range of diseases. Expert authors provide insight into the care of patients with pre-existing medical conditions that fail in some cases to adapt as well as offer insights into how high altitude research can help critically ill patients. High Altitude: Human Adaptation to Hypoxia is an important new volume that offers a window into greater understanding and more successful treatment of hypoxic human diseases